Preparation method of low-hydroxyl high-purity synthetic quartz sand

By using reforming and shaping devices and water vapor generators in the preparation process of synthetic quartz sand, combined with the calcination and purification steps, the problem of difficult control of particle distribution, hydroxyl groups and residual carbon quantity is solved, and the preparation of low-hydroxyl groups and high-purity quartz sand is achieved, suitable for quartz crucible raw materials.

CN119706851APending Publication Date: 2025-03-28CHINA CATALYST HLDG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411968360.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing synthetic quartz sand technology is difficult to control particle distribution and reduce the number of hydroxyl groups and residual carbon, resulting in defects such as bubble coverings and high hydroxyl groups in quartz products, limiting their widespread application.

Method used

Using reforming and shaping devices and water vapor generators, synthetic quartz sand with low hydroxyl groups and high purity were prepared by reforming and surface treatment of wet gels, combined with calcining and purification steps.

Benefits of technology

It effectively improves the particle size and compactness of synthetic quartz sand, reduces the number of hydroxyl groups and residual carbon, and obtains low-hydroxyl groups and high-purity quartz sand, suitable for quartz crucible raw materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706851A_ABST
    Figure CN119706851A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of low-hydroxyl high-purity synthetic quartz sand, and belongs to the technical field of chemical production. Comprising the following steps: S1, preparing wet gel; s2, reforming and shaping; s3, surface treatment; s4, roasting is carried out; and S5, purifying. The effective method solves the problems of high carbon residue, hydroxyl number, wide ideal particle size range and low yield of the traditional synthetic quartz sand. A wet gel colloid is synthesized by controlling a proper proportion of silicon alkoxide, a water solvent, trace quartz sand, silicon powder and the like, and the synthetic quartz sand with high purity, high bulk density, proper particle size and lower hydroxyl content is directly obtained by combining the reforming and shaping device and the water vapor generator device under the disturbance of heating airflow and combining a proper roasting way and a purification way. The method is a more effective preparation method applied to industrial amplification production of synthetic quartz sand.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of synthetic quartz sand, and in particular to a method for preparing low-hydroxyl high-purity synthetic quartz sand. Background Art

[0002] High-purity quartz sand usually refers to quartz powder with a silicon dioxide content higher than 4N8, and the general particle size is 100-300μm. It is an indispensable and irreplaceable important functional material in the semiconductor, optical fiber, photovoltaic, optical, electric light source and other industries. High-purity quartz sand is mainly obtained by purifying natural quartz ore. Due to its complex composition, it is difficult to purify it to more than 5N. The requirements for the purity of quartz glass products in semiconductors and photovoltaics are getting higher and higher, and it is difficult to improve the natural purification method. In addition, due to the limitation of natural resources, in the long run, synthetic quartz sand is the only technical path that is not subject to human control.

[0003] Mitsubishi Chemical Corporation of Japan has used the sol-gel method to obtain raw materials for semiconductor quartz crucibles, even reaching 7N or above. The sol-gel method has been widely recognized, for example, I. Matsuyama and K. Susa, Syntheses of high-purity silica glass by the sol-gel method, Am. Ceram. Soc. Bull., 1984 (11): 1408-1411. Generally speaking, the quartz powder produced by this process has a much lower impurity concentration than the natural quartz powder commonly used in quartz glass smelting. In addition, the quartz glass prepared from synthetic quartz sand prepared by the molten sol-gel method has neither light absorption nor corresponding photoluminescence at about 240nm, which is caused by oxygen vacancies. The synthetic quartz sand prepared by the sol-gel method is significantly purer and has excellent optical properties.

[0004] However, although it has higher purity than the synthetic sand prepared by the water glass method, the quartz sand synthesized by this synthesis method is mainly amorphous. Compared with natural quartz, it has poor service life, hardness, and temperature resistance. In particular, when using TEOS and TMOS organosilicon salt hydrolysis, the residual carbon and hydroxyl groups in the synthetic quartz powder during the high-temperature melting process are easy to generate gases such as CO2, CO, and H2O, causing quartz products to be bubble-coated and have a large number of hydroxyl groups. This has always been a technical bottleneck, limiting its wide application. Therefore, researching and developing a synthetic quartz sand with low hydroxyl and high purity properties similar to natural quartz sand has great prospects and significance.

[0005] As we all know, to determine whether a batch of synthetic sand can be used as a raw material for quartz crucibles, not only its purity is considered, but also its particle size, number of hydroxyl groups, and number of residual carbon. In existing technical literature, the main synthetic quartz sands are amorphous. In actual verification, the synthetic quartz sand obtained by this sol-gel method has not been verified by crucible manufacturers except for Mitsubishi MKC synthetic sand. Some literature also mentions that when a small amount of cristobalite crystal phase is added, low-hydroxyl synthetic quartz sand will be obtained, such as patents JP2586973B2 and JP2839725B2, which prove that cristobalite synthetic quartz sand has a lower hydroxyl number. However, there are few reports on equipment or methods that can control particle distribution and reduce the number of hydroxyl groups and residual carbon.

[0006] In summary, it is urgent to invent and develop a preparation method that solves these problems. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing low-hydroxyl high-purity synthetic quartz sand, which solves the problem that conventional synthesis technology cannot control particle distribution and can reduce the number of hydroxyl groups and the amount of residual carbon.

[0008] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0009] The present invention provides a method for preparing low-hydroxyl high-purity synthetic quartz sand, comprising the following steps:

[0010] S1, preparing wet gel; S2, reshaping; S3, surface treatment; S4, calcination; S5, purification;

[0011] In S2 and S3, reforming and shaping and surface treatment are achieved through a reforming and shaping device and a water vapor generator;

[0012] The forming device comprises a cylindrical structure, a shaping conical surface arranged in the cylindrical structure, a scraper arranged in the cylindrical structure and close to the shaping conical surface, a driving mechanism for driving the scraper to rotate along the surface of the shaping conical surface, and a filtering inclined plate arranged below the shaping conical surface;

[0013] A feed port for introducing wet gel is provided at the top of the cylindrical structure, and an air inlet connected to the water vapor generator is provided on the middle side wall thereof; a discharge port close to the inclined lower end of the filtering inclined plate is provided at the bottom of the cylindrical structure; in this embodiment, a circular slide rail is prefabricated on the outer peripheral wall of the shaping cone surface, and the end of the scraper slides in the circular slide rail through a ball bearing.

[0014] Preferably, the water vapor generator comprises a solution container, a liquid inlet arranged on the solution container, an air supply pipe connected to the interior of the solution container, an exhaust pipe connected to the air supply pipe and the solution container respectively, and a heater for heating the gas in the exhaust pipe; wherein the air supply pipe is connected to the interior of the solution container through a first branch pipe, and is also connected to the exhaust pipe through a second branch pipe; a first valve and a first flow meter are arranged on the first branch pipe, and a second valve and a second flow meter are arranged on the second branch pipe; wherein the lower end of the first branch pipe penetrates 1 / 3 of the depth of the alkaline solution container; specifically, it can be above the liquid surface; wherein the first valve and the second valve are both solenoid valves, and are respectively controlled by a controller based on the detection value of the flow meter. Mixed water vapor is generated here, and enters the primary particle group formed by the flat cone surface in the forming device to contact, further condense and age; here, it quickly contacts the alkaline solution in the air flow generated by the water vapor generator, and the primary particle group is further compacted and sphericalized, and secondary particle group particles are formed from the discharge port.

[0015] Preferably, a plurality of fine holes are evenly formed on the shaping cone surface, and the aperture range is 0.3-1.5 mm; wherein the scraper is an inverted V-shaped structure; the distance between the scraper and the flat cone surface is 0.15-1.1 mm; the driving mechanism includes a rotating shaft connected to the scraper, and a speed regulating motor arranged at the top of the cylindrical structure and used to drive the rotating shaft; prefabricated holes are evenly formed on the filtering inclined plate, and the aperture is 200-300 mesh; a receiving cavity is arranged below the filtering inclined plate, and a baffle is arranged at the bottom of the receiving cavity. In this embodiment, the baffle is used as a hinge baffle, and a small amount of fine powder below the filtering inclined plate will be graded from here, and discharged regularly by opening the baffle.

[0016] Preferably, the control flow setting range of the first flowmeter is 5-75ml / min, the control flow setting range of the second flowmeter is 10-125ml / min, and the gas entering the gas supply pipe is one or more of nitrogen, air, helium, and argon; the heating range of the heater is 30-200°C, wherein the contact time between the alkaline solution sprayed from the water vapor generator and the primary particle group in the reforming and shaping in S2 is 1-5min; the solution container is injected with an alkaline solution, and the alkaline solution includes one or more of an ammonia solution, a nitrogen-containing alkylamine, pyridine, monomethylamine, dimethylamine, and trimethylamine; wherein the concentration of the alkaline solution is 0.01-30%.

[0017] Preferably, in S1, when preparing the wet gel, one or more of the following methods are mixed: silicon alkoxide hydrolysis method, water glass method, and silicon powder hydrolysis method; the raw materials for preparing the wet gel include quartz powder, wet grinding dispersion medium, ethyl silicate, ultrapure water, and additives.

[0018] Preferably, in S2, the wet gel obtained in S1 is reshaped by a molding device to prepare a primary particle mass.

[0019] Preferably, in S3, the primary particle mass obtained in the forming device is contacted with an appropriate alkaline solution, and then screened and graded to remove excess low-particle-size fine powder to prepare a secondary particle mass.

[0020] Preferably, in S4, the secondary particle mass obtained in S3 is sintered, and the sintering equipment includes one or more of a rotary furnace, a muffle furnace, a vacuum furnace, a dehydroxylation furnace, a chlorination furnace, and an atmosphere furnace, and the sintering temperature is 650-1450°C and the sintering time is 4-48h to obtain synthetic quartz sand.

[0021] Preferably, in S5, the synthetic quartz sand obtained in S4 is further purified to obtain high-purity synthetic quartz sand. In S5, the purification method includes one or more of acid washing, high-temperature purging, chlorination treatment, and dehydroxylation treatment.

[0022] Compared with the prior art, the beneficial technical effects of the present invention are:

[0023] The present invention is combined with a reforming and shaping device to effectively improve the ideal yield of synthetic quartz sand particle size; through the water vapor generator device, different from the traditional drying and roasting methods, it is more efficient in reducing residual carbon and improving density, and improving the looseness of particles, low hydroxyl and high purity. Specifically, it is an effective preparation method for industrial scale-up production of low hydroxyl and high purity synthetic quartz sand. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The present invention will be further described below in conjunction with the accompanying drawings.

[0025] Figure 1 The present invention is a step-by-step diagram of a method for preparing low-hydroxyl high-purity synthetic quartz sand.

[0026] Figure 2 yes Figure 1 Schematic diagram of the structure of the medium reforming and shaping device and the surface treatment water vapor generating device.

[0027] Figure 3 This is the X-ray diffraction spectrum of the synthetic quartz sand in Example 1.

[0028] In the figure, 1. reforming and shaping device; 2. feed inlet; 3. shaping cone; 4. motor; 5. fine pores; 6. filtering inclined plate; 7. baffle; 8. air inlet; 9. discharge port; 10. water vapor generator; 11. air supply pipe; 12. liquid inlet; 13. heater; 14-1. first valve; 14-2. second valve; 15-1. first flow meter; 15-2. second flow meter; 16. scraper; 17. solution container. DETAILED DESCRIPTION

[0029] Example 1

[0030] 1) Wet gel preparation

[0031] Preparation of high-purity quartz powder: quartz powder with a purity of ≥99.94% and a particle size of 10-40μm is used in a SJM-5L stirring ball mill (wholly lined with polyurethane), with zirconium oxide balls: Ф3mm; wet grinding dispersion medium: ultrapure water. The weight ratio of quartz powder to ultrapure water is 1:2; the speed is 600r / min, and the duration is 12h. Subsequently, it is washed 3 times with 5wt% hydrochloric acid solution, each time for 1h, and then washed 3 times with ultrapure water, and dried to obtain 0.6-1μm high-purity quartz powder ≥99.99%).

[0032] Slurry preparation: Purified (>99.99%) ethyl silicate, ultrapure water, the above-mentioned quartz powder, and an auxiliary agent, lactic acid (>99.99%), are stirred in a vacuum stirrer for 3 hours; the molar ratio of ethyl orthosilicate, ultrapure water, and lactic acid is 1:12:0.075, and the amount of quartz powder added is 0.05%, to prepare an emulsion slurry with a viscosity of 100 mPa·s.

[0033] Shaping: Incubate at 90°C for 24 hours to obtain a wet gel block, which is then mechanically broken into 0.5-5 mm gel particles.

[0034] 2) Reshaping & surface treatment

[0035] The gel particles in step 1) are fed through the reforming and shaping device at a rate of 1.5kg / min. At the same time, purified air is used as a carrier gas, and the first flow meter is set to a flow rate of 23ml / min; the second flow meter is set to a flow rate of 42ml / min; the alkaline solution concentration is 12.5% ​​ammonia solution, and at this time, the ammonia solution used contains 4-25ppm of alkaline metal ions; the air carrier gas is brought to the heater through the air flow, heated to 120°C, and the primary particle cluster that passes through the fine pores of the shaping cone after the scraper reforming and shaping is purged through the feed port of the shaping device. Because it contains a small amount of water vapor with a certain temperature, the fine powder on the surface of the primary particle cluster and between the particles is separated. On the one hand, the surface of the primary particle cluster and the ammonia solution are further hardened to make it dense. On the other hand, less than 10ppm of alkaline metal ions are adsorbed on the surface of the primary particle cluster, and are graded with the help of the filtering inclined plate. After hardening, they are dispersed to obtain secondary particle clusters from the discharge port of the reforming and shaping device.

[0036] 3) Calcination

[0037] In this embodiment, if the purity of the silicon source is high, the roasting can be performed by adding 2L / min / kg of purified air atmosphere to the roasting curve. Impurities contained in the silicon source less than 10ppm can be easily carried away by the airflow, thereby achieving purification. The secondary particle mass obtained in step 2 is calcined at 300°C for 5h, 500°C for 5h, 900°C for 10h, 1250°C for 2h, and 1350°C for 5h to be converted into high-purity synthetic quartz sand.

[0038] like Figure 3 The synthetic quartz sand obtained in Example 1 was found to be a cristobalite crystal phase, and therefore had similar properties to natural quartz sand, with a bulk density of 1.32 g / cm 3 , the true density is 2.21g / cm 3 , total impurity content is less than 1ppm, hydroxyl 27ppm; residual carbon 11ppm.

[0039] 4) Detection:

[0040] Crystalline phase: An X-ray diffractometer was produced by PANalytical B.V. of the Netherlands.

[0041] Hydroxyl number (ppm): Particles were detected using FTIR at a wavelength of 3600 cm -1 The infrared absorption intensity at the left and right sides is converted using the Lambert-Beer law.

[0042] Embodiment 2:

[0043] According to Example 1, the synthetic process is similar, with the following specific differences: the molar ratio of purified methyl silicate, ultrapure water, and lactic acid is 1:16:0.075, and the above-mentioned quartz powder is replaced with silica powder, and the addition amount is 0.05%. Among them, the silica powder is prepared as follows: 1 kg of purified ethyl silicate, 2L of ethanol, 660g of ultrapure water, and 500g of ammonia water are mixed, stirred at room temperature for 15 hours, and after hydrolysis, dried at 140°C for 24 hours, and calcined at 1050°C for 5 hours in a muffle furnace at a heating rate of 200°C / H. The calcined powder is crushed with a ball mill made of quartz glass to prepare an average particle size of 0.5-1.6um.

[0044] Similarly, after calcination, no further purification treatment is required. The synthetic quartz sand obtained is measured to be a cristobalite crystalline phase with a bulk density of 1.31 g / cm 3 , true density is 2.20g / cm 3 , total impurity content is less than 1ppm, hydroxyl 32ppm; residual carbon 12ppm.

[0045] Comparative Example 1:

[0046] According to Example 1, the synthesis process is similar, with the following specific differences: the molar ratio of purified methyl silicate, ultrapure water, and hydrochloric acid is 1:16:0.025, and the above-mentioned quartz powder is replaced with silica powder, and the addition amount is 0.025%. Among them, the silica powder is prepared as follows: 3kg of commercially available water glass, with a solid content of 29.48% and a viscosity of 176cps; slowly drip it into 1L16.3wt% sulfuric acid solution, add 35g50.2wt% hydrogen peroxide, stir for 15min, then heat it to 50℃, stir for 30min to precipitate the precipitate, and then wash the precipitate twice with 1L ultrapure water and filter it. Add 0.5L24.5% sulfuric acid aqueous solution, add 1.5g citric acid, 20.8g50.3% hydrogen peroxide, and stir evenly for 10min. Heat it to 70℃, stir for 1h, filter it, wash it twice with ultrapure water, and dry it at 125℃ for 24h. The silicon powder was obtained by calcining at 1050°C for 5 hours.

[0047] Because water glass is a silicon source, its purity needs to be considered. Therefore, after calcination, it needs further purification treatment. The high-temperature atmosphere treatment method will affect the transparency of the final synthetic quartz sand. That is, the calcination curve is adjusted to calcination at 300℃ for 5h, 500℃ for 5h, 800℃ for 10h, 900℃ for 5h, 1100℃ for 20h, and 1200℃ for 2h, which is converted into high-purity synthetic quartz sand.

[0048] Further, purification was performed in the following manner, and the specific operation was as follows:

[0049] One pickling, liquid-to-solid ratio 1:5; 0.25M hydrofluoric acid, 1M hydrochloric acid, 0.5M nitric acid; chlorination treatment in a roasting furnace, using 2 times the mass ratio of high-purity ammonium fluoride as the chlorine source, roasting in a chlorination furnace at 900-1000℃ for 2h.

[0050] Secondary acid washing, liquid-to-solid ratio 1:3; 0.25M hydrofluoric acid, 0.5M hydrochloric acid, 1.5M oxalic acid; use ultrapure water to wash until neutral, and dry at 200℃ for 24h.

[0051] The synthetic quartz sand obtained was measured to be a cristobalite crystal phase with a bulk density of 1.27 g / cm 3 , true density is 2.20g / cm 3 , total impurity content is less than 1ppm, hydroxyl 24ppm; residual carbon 5ppm.

[0052] Comparative Example 2:

[0053] In a dry 50L four-necked flask, put purified methyl silicate, ultrapure water, and citric acid in a molar ratio of 1:12:0.075, stir at 30°C for 3 hours, raise the temperature of the reactor to above 50°C, concentrate the solution for 8 hours, and obtain a sol solution with a water content of less than 21%; keep it at 90°C for 24 hours to obtain wet gel blocks, and then mechanically break them into 0.5-5mm gel particles.

[0054] After calcination at 300℃ for 5h, 500℃ for 5h, 700℃ for 5h, 900℃ for 10h, and 1200℃ for 30h, the obtained synthetic quartz sand was found to be amorphous with a bulk density of 1.23 g / cm 3 , the true density is 1.970g / cm 3 , total impurity content is less than 1ppm, hydroxyl 83ppm; residual carbon 125ppm.

[0055] The above embodiments are only descriptions of the preferred methods of the invention, and are not intended to limit the scope of the invention. Without departing from the design spirit of the invention, various modifications and improvements made to the technical solutions of the invention by ordinary technicians in this field should fall within the protection scope of the claims of the invention.

Claims

1. A method for preparing low-hydroxyl high-purity synthetic quartz sand, characterized in that: The steps include: S1, preparing wet gel; S2, reorganization and finalization; S3, surface treatment; S4, roasting; S5, purification; In S2 and S3, reforming and shaping and surface treatment are achieved through a reforming and shaping device and a water vapor generator; The forming device (1) comprises a cylindrical structure, a shaping conical surface (3) arranged in the cylindrical structure, a scraper (16) arranged in the cylindrical structure and close to the shaping conical surface (3), a driving mechanism for driving the scraper (16) to rotate along the surface of the shaping conical surface (3), and a filtering inclined plate (16) arranged below the shaping conical surface (3); A feed port (2) for introducing wet gel is provided at the top of the cylindrical structure, an air inlet (8) connected to the water vapor generator is provided on the middle side wall thereof; and a discharge port (9) close to the inclined lower end of the filtering inclined plate (16) is provided at the bottom of the cylindrical structure.

2. The method for preparing low-hydroxyl high-purity synthetic quartz sand according to claim 1, characterized in that: The water vapor generator comprises a solution container (17), a liquid inlet (12) arranged on the solution container (17), an air supply pipe (11) connected to the interior of the solution container (17), an exhaust pipe connected to the air supply pipe (11) and the interior of the solution container (17), and a heater (13) for heating the gas in the exhaust pipe; wherein the air supply pipe (11) is connected to the interior of the solution container (17) through a first branch pipe, and is also connected to the exhaust pipe through a second branch pipe; a first valve (14-1) and a first flow meter (15-1) are arranged on the first branch pipe, and a second valve (14-2) and a second flow meter (15-2) are arranged on the second branch pipe.

3. The method for preparing low-hydroxyl high-purity synthetic quartz sand according to claim 1, characterized in that: A plurality of fine holes (5) are evenly formed on the shaping conical surface (3), and the hole diameter ranges from 0.3 to 1.5 mm; The scraper (16) is an inverted V-shaped structure; the distance between the scraper (16) and the flat cone surface (3) is 0.15-1.1 mm; The driving mechanism comprises a rotating shaft connected to the scraper (16), and a speed regulating motor (4) arranged at the top of the cylindrical structure and used for driving the rotating shaft; Prefabricated holes are evenly opened on the filtering inclined plate (6), and the hole diameter is 200-300 meshes; a material receiving cavity is arranged below the filtering inclined plate (6), and a baffle (7) is arranged at the bottom of the material receiving cavity.

4. The method for preparing low-hydroxyl high-purity synthetic quartz sand according to claim 2, characterized in that: The control flow setting range of the first flow meter (15-1) is 5-75 ml / min, the control flow setting range of the second flow meter (15-2) is 10-125 ml / min, and the gas entering the gas supply pipe (11) is one or more of nitrogen, air, helium, and argon; The heating range of the heater (13) is 30-200°C, wherein the contact time between the alkaline solution sprayed from the water vapor generator (10) and the primary particle group in the reforming and shaping in S2 is 1-5 minutes; The solution container (17) is filled with an alkaline solution, wherein the alkaline solution includes one or more of an ammonia solution, a nitrogen-containing alkylamine, pyridine, monomethylamine, dimethylamine, and trimethylamine; The concentration of the alkaline solution is 0.01-30%.

5. The method for preparing low-hydroxyl high-purity synthetic quartz sand according to claim 1, characterized in that: In S1, when preparing the wet gel, one or more of the following methods are used in combination: silicon alkoxide hydrolysis method, water glass method, and silicon powder hydrolysis method; the raw materials for preparing the wet gel include quartz powder, wet grinding dispersion medium, ethyl silicate, ultrapure water, and additives.

6. The method for preparing low-hydroxyl high-purity synthetic quartz sand according to claim 2, characterized in that: In S2, the wet gel obtained in S1 is reshaped by a forming device (1) to prepare a primary particle mass.

7. The method for preparing low-hydroxyl high-purity synthetic quartz sand according to claim 6, characterized in that: In S3, the primary particle mass obtained in the forming device (1) is contacted with an appropriate alkaline solution, and then screened and graded to remove excess low-particle-size fine powder, thereby preparing a secondary particle mass.

8. The method for preparing low-hydroxyl high-purity synthetic quartz sand according to claim 7, characterized in that: In S4, the secondary particle mass obtained in S3 is sintered, and the sintering equipment includes one of a rotary furnace, a muffle furnace, a vacuum furnace, a dehydroxylation furnace, a chlorination furnace, and an atmosphere furnace, and the sintering temperature is 650-1450°C and the sintering time is 4-48h to obtain synthetic quartz sand.

9. The method for preparing low-hydroxyl high-purity synthetic quartz sand according to claim 8, characterized in that: In S5, the synthetic quartz sand obtained in S4 is further purified to obtain high-purity synthetic quartz sand.

10. The method for preparing low-hydroxyl high-purity synthetic quartz sand according to claim 9, characterized in that: In S5, the purification method includes one or more of acid washing, high temperature purging, chlorination treatment, and dehydroxylation treatment.

Citation Information

Patent Citations

  • How to produce cristobalite

    JP2586973B2

  • Method for manufacturing high-purity crystalline silica

    JP2839725B2